Eicosapentaenoic acid attenuates cigarette smoke-induced lung inflammation by inhibiting ROS-sensitive inflammatory signaling - Liu, Meng-Han; Lin, An-Hsuan; Lu, Shing-Hwa; Peng, Ruo-Yun; Lee, Tzong-Shyuan; Kou, Yu Ru (Frontiers in Physiology, 2014)
Cigarette smoking causes chronic lung inflammation that is mainly regulated by redox-sensitive pathways. Our previous studies have demonstrated that cigarette smoke (CS) activates reactive oxygen species (ROS)-sensitive mitogen-activated protein kinases (MAPKs)/nuclear factor-B (NF-B) signaling resulting in induction of lung inflammation. Eicosapentaenoic acid (EPA), a major type of omega-3 polyunsaturated fatty acid, is present in significant amounts in marine-based fish and fish oil. EPA has been shown to possess antioxidant and anti-inflammatory properties in vitro and in vivo. However, whether EPA has similar beneficial effects against CS-induced lung inflammation remains unclear. Using a murine model, we show that subchronic CS exposure for 4 weeks caused pulmonary inflammatory infiltration (total cell count in bronchoalveolar lavage fluid (BALF), 11.0-fold increase), increased lung vascular permeability (protein level in BALF, 3.1-fold increase), elevated levels of chemokines (11.4- to 38.2-fold increase) and malondialdehyde (an oxidative stress biomarker; 2.0-fold increase) in the lungs, as well as lung inflammation; all of these CS-induced events were suppressed by daily supplementation with EPA. Using human bronchial epithelial cells, we further show that CS extract (CSE) sequentially activated NADPH oxidase (NADPH oxidase activity, 1.9-fold increase), increased intracellular levels of ROS (3.0-fold increase), activated both MAPKs and NF-kappaB, and induced interleukin-8 (IL-8; 8.2-fold increase); all these CSE-induced events were inhibited by pretreatment with EPA. Our findings suggest a novel role for EPA in alleviating the oxidative stress and lung inflammation induced by subchronic CS exposure in vivo and in suppressing the CSE-induced IL-8 in vitro via its antioxidant function and by inhibiting MAPKs/NF-kappaB signaling.